2020
DOI: 10.1371/journal.pone.0233634
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with unmet fertility desire and perceptions of ideal family size among women in Bangladesh: Insights from a nationwide Demographic and Health Survey

Abstract: Introduction Along with the developing world, Bangladesh has made a tremendous improvement in declining total fertility rate, however, this declining trend is not uniform to all the socio-demographic stratum. Incongruities exist between the numbers of children that women bearing and what they actually desired which refers to unmet fertility desire. This study aims to elicit women's perception of ideal number of children and predictors of unmet fertility desire in Bangladesh. Method This study analyzed national… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 31 publications
4
17
2
Order By: Relevance
“…11 26 Concerning the perceived ideal number of children, negative attitudes towards wife-beating and the right to refuse sex result in a smaller number of children in many African nations. 11 17 The same is reflected in the present study given that negetive attitude towards wife beating strengthen women's status in their families. The same outcome is likely for other developing countries in Southeast Asia and sub-Saharan Africa.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…11 26 Concerning the perceived ideal number of children, negative attitudes towards wife-beating and the right to refuse sex result in a smaller number of children in many African nations. 11 17 The same is reflected in the present study given that negetive attitude towards wife beating strengthen women's status in their families. The same outcome is likely for other developing countries in Southeast Asia and sub-Saharan Africa.…”
Section: Discussionsupporting
confidence: 82%
“… 27 A study focusing on Bangladesh with similar empowerment measures found a significant association with unmet fertility desire. 17 These results demonstrated that women’s final voice in the daily household purchase has sufficient independent explanatory power to explain fertility preferences beyond traditional measures of women status, for example, education and employment status. Another empowerment measure, negative attitude towards wife-beating, was associated with a small ideal number of children in Guinea and Zambia; however, negative attitude towards refusal of sex was found to be associated with greater odds of having more children than desire in Namibia and Zambia and lower odds than desire in Mali.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…The child marriage rate in Bangladesh gradually declined from 66% in 2014 to 59% in 2017 [ 1 , 18 ]. However, the continued high prevalence of child marriage and adolescent motherhood rates could delay the possibility of achieving the SDGs on child and women’s health [ 7 , 19 , 20 ]. There is a pressing need to evaluate the existing policy for necessary adjustment and targeting intervention programs to keep Bangladesh on track to achieve pertinent SDGs by 2030 before it is too late.…”
Section: Introductionmentioning
confidence: 99%